Determinan Insiden Sindrom Metabolik Menurut Gender - Ratih Oemiati (Jurnal Persada Husada Indonesia, 2019)
Gender differences in Metabolic Syndrome contribute to cardiovascular disease and type 2 Diabetes Mellitus. The prevalence of Metabolic Syndrome in Asia ranges from 10-15%, while in Indonesia as much as 23.34%. Of the total population experiencing metabolic syndrome, 26.2% occur in males and 21.4% in females. Research in Jakarta, as the capital and largest city of Indonesia, has a metabolic syndrome prevalence of 28.4%. This study aims to describe the determinants of Metabolic Syndrome according to gender from sociodemographic, demographic, lifestyle, and food intake independent variables. Furthermore BMI will be analyzed which is followed for 3 years by sex with General Mode of Linear SPSS version 20. This study is a sub-sample of the Non-communicable Disease Risk Factor Cohort Study conducted by the Research Center for Public Health Efforts, Health Research and Development Agency, in 2014 in the city Bogor. A total of 1385 complete data were analyzed and 160 new cases (incidents) were found in 2014, with details of 39 men and 121 women. The incidence of Metabolic Syndrome in 2014 was 11.9%, where 3% occurred in men and 8.9% occurred in women. There are differences in age groups in the incidence of Metabolic Syndrome in men who are targeting the older group compared to younger women in their age group. In the carbohydrate intake of both gender groups were equally greater in the> 60% category with almost the same percentage, but in the fat intake was higher in males for the > 25% category. GLM analysis for BMI in men and women differed in the higher start in women but the pattern of improvement was the same from follow up 1 to 3.